2016
DOI: 10.1556/0806.44.2016.019
|View full text |Cite
|
Sign up to set email alerts
|

Cerealn-glycoproteins Enrichment by Lectin Affinity Monolithic Chromatography

Abstract: Research of cereal glycoproteins is important for understanding of their functional properties, their role during technological processing of cereals and it can serve as a valuable tool for the detection of cereal allergens. The main intention of this study was the screening of profile of water-soluble glycoproteins present in barley (Hordeum vulgare), wheat durum (Triticum durum) and spelt (Triticum spelta). Lectin monolithic HPLC column was used for rapid and effective enrichment of glycoprotein fractions. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Generally, lectin affinity chromatography in various combinations with gel electrophoresis, liquid chromatography (LC), and MS techniques is the most widespread approach for glycoprotein analysis. 65,66 In quantitative proteomics, the iTRAQ method showed differential expression of selected barley allergenic proteins (e.g., pUP38, barwin) during food processing. 57 The methods used in proteomics are also applicable to glycoproteomics.…”
Section: Post-translational Modifications Of Barley Proteins and Diff...mentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, lectin affinity chromatography in various combinations with gel electrophoresis, liquid chromatography (LC), and MS techniques is the most widespread approach for glycoprotein analysis. 65,66 In quantitative proteomics, the iTRAQ method showed differential expression of selected barley allergenic proteins (e.g., pUP38, barwin) during food processing. 57 The methods used in proteomics are also applicable to glycoproteomics.…”
Section: Post-translational Modifications Of Barley Proteins and Diff...mentioning
confidence: 99%
“…The well-known proteomics approaches include MALDI-TOF, SDS-PAGE, 2D differential gel electrophoresis (DIGE), MS, two-dimensional gel electrophoresis (2DE), LC-MS/MS LC-ESI-MS/MS, iTRAQ, and peptide mass fingerprinting (PMF) have been applied in barley to determine PTMs. , Several published results confirmed that a combination of multiple omics approaches could be beneficial in identifying potential candidate genes, their pathways, and the covalent modification of proteins. Generally, lectin affinity chromatography in various combinations with gel electrophoresis, liquid chromatography (LC), and MS techniques is the most widespread approach for glycoprotein analysis. , In quantitative proteomics, the iTRAQ method showed differential expression of selected barley allergenic proteins (e.g., pUP38, barwin) during food processing …”
Section: Post-translational Modifications Of Barley Proteins and Diff...mentioning
confidence: 99%
“…In fact, there are a number of lectin-based monolithic columns that are now commercially available. Concanavalin A (ConA) HPLC column (ProSwift ® ConA-1S monolith column by Thermo Scientific, Waltham, MA, USA) was used to design a protocol using lectin HPLC-GE-MALDI-TOF MS/MS that includes gel electrophoresis (GE) separation, MS detection, and consequential bioinformatic analysis to screen total N-glycoprotein "pool" in cereals [99]. The analysis was also done on water-soluble glycoproteins from wheat durum (Triticum durum), barley (Hordeum vulgare), and spelt (Triticum spelta).…”
Section: Lectin Affinity-based Monolithic Materialsmentioning
confidence: 99%